The Epstein-Barr Virus (EBV) gN Homolog BLRF1 Encodes a 15-Kilodalton Glycoprotein That Cannot Be Authentically Processed unless It Is Coexpressed with the EBV gM Homolog BBRF3 - Lake, Cathleen M. (American Society for Microbiology, 1998)
The Epstein-Barr virus (EBV) homolog of the conserved herpesvirus glycoprotein gN is predicted to be encoded by the BLRF1 open reading frame (ORF). Antipeptide antibody to a sequence corresponding to residues in the predicted BLRF1 ORF immunoprecipitated a doublet of approximately 8 kDa from cells expressing the BLRF1 ORF as a recombinant protein. In addition, four glycosylated proteins of 113, 84, 48, and 15 kDa could be immunoprecipitated from virus-producing cells by the same antibody. The 15-kDa species was the mature form of gN, which carried α2,6-sialic acid residues. The remaining glycoproteins which associated with gN were products of the BBRF3 ORF of EBV, which encodes the EBV gM homolog. The 8-kDa doublet seen in cells expressing recombinant gN comprised precursors of the mature 15-kDa gN. Coexpression of EBV gM with EBV gN was required for authentic processing of the 8-kDa forms to the 15-kDa form.